Human Capital Development and SME Innovation in Indonesia: The Contingent Roles of Financial and Managerial Practices - M Fahmi (Journal of Business Innovation and Accounting Research, 2026)
Purpose: This study examines how human capital development is associated with innovation capability and business performance among Indonesian small and medium-sized enterprises (SMEs), and whether financial and managerial practices condition these relationships. Design/methodology/approach: A sequential explanatory mixed-methods design combined survey responses from 285 SMEs with in-depth interviews involving 35 respondents. Quantitative analysis used descriptive statistics, multiple regression, and partial least squares structural equation modeling (PLS-SEM); qualitative data were analyzed thematically to interpret the statistical patterns. Findings: Human capital development was positively associated with innovation capability (β = .412, p < .001), and innovation capability was positively associated with business performance (β = .389, p < .001). The indirect association between human capital and performance through innovation capability was significant (β = .160, p < .001), while the direct association remained significant (β = .198, p = .001), a pattern consistent with partial statistical mediation. Financial practices strengthened the human capital–innovation relationship (β = .187, p = .004), whereas managerial practices strengthened the innovation–performance relationship (β = .213, p < .001). Interviews indicated that employee development, financing constraints, and digital competencies were central to firms’ innovation experiences. Originality/value: The study integrates human capital theory, the resource-based view, and dynamic capabilities reasoning to explain not only whether human capital relates to SME outcomes, but also how innovation transmits this relationship and under what organizational conditions it becomes stronger in an emerging-market setting.